(untitled) (Journal of Applied Juvenile Justice Services, 2025)
Objective: Youth in contact with the justice system have higher rates of risky behaviors such as substance use than youth not in contact, yet the mechanisms underlying these behaviors are not clearly understood. Research with incarcerated and post-adjudicated adolescent samples have examined some of the individual level factors by examining the relationship between psychosocial maturity and substance use; however, adolescents at point of first contact with the juvenile justice system, a crucial point of intervention and diversion, have been given little attention. Method: The current study examined the relationship between psychosocial maturity, including emotion regulation, and high-risk behaviors such as substance use and delinquency in court-involved, non-incarcerated youth at point of first juvenile court contact. Results: MANCOVA analyses and logistic regressions partially supported our hypotheses that lesser psychosocial maturity was associated with earlier onset of substance use and increased delinquent behaviors. Conclusion: Findings inform potential intervention needs around specific elements of psychosocial maturity for youth involved in the justice system.